2006
DOI: 10.1007/s10658-005-5804-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climatic Factors on Powdery Mildew Caused by Sphaerotheca macularis f. sp. Fragariae on Strawberry

Abstract: Powdery mildew of strawberry is caused by the obligate pathogenic fungus Sphaerotheca macularis f. sp. fragariae. The disease affects the leaves, flowers and fruit of this crop. This study examined the effects of different environmental factors on disease cycle components (germination, conidiation and survival) in strawberry to determine which conditions limit the progress of the disease. The optimal environmental conditions for conidial germination and conidial germ tube length ranged between 15 and 25°C with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 15 publications
2
53
1
Order By: Relevance
“…Sphaerotheca macularis f. sp fragariae) (Boesewinkel, 1979;Xiao et al, 2001;Foulongne et al, 2003;Turechek et al, 2004). PM in strawberry is caused by the obligate pathogenic fungus S. macularis f. sp fragariae, and affects leaves, flowers, and fruit (Amsalem et al, 2006). These four fungi cause similar PM symptoms (Pessina et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sphaerotheca macularis f. sp fragariae) (Boesewinkel, 1979;Xiao et al, 2001;Foulongne et al, 2003;Turechek et al, 2004). PM in strawberry is caused by the obligate pathogenic fungus S. macularis f. sp fragariae, and affects leaves, flowers, and fruit (Amsalem et al, 2006). These four fungi cause similar PM symptoms (Pessina et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The average light intensity was 50 percent higher in the "free" canopy around bloom time and increased to four-fold of that in the VSP trellising in the following weeks. Radiation, and especially UV radiation, was shown to inhibit the development of several fungi, both biotrophs (Rotem et al 1985;Jacob et al 2008;Amsalem et al 2006) and necrotrophs (Stevenson and Pennypacker 1988), the former including E. necator (Willocquet et al 1996). Light is also assumed to affect the chemical composition of grapes.…”
mentioning
confidence: 99%
“…In tomato we found that some of the cultivars were more resistant to O. neolycopersicy than others (Jacob et al 2008). In a crop such as strawberry (Amsalem et al 2005) different resistance sources are available. On the contrary, in the present work there was no significant difference in resistance.…”
Section: Discussionmentioning
confidence: 86%
“…In various studies, temperatures allowing for powdery mildew development have been shown to range from 15-25°C, with an optimum of approximately 20°C in strawberry (Amsalem et al 2005;Okayama et al 1995) or 22-23°C in rose (Xu 1999a,b). Temperatures of 10°C and 30°C and above have been shown to be detrimental to the pathogen and disease incidence was significantly reduced under these conditions (Amsalem et al 2005;Elad et al 2007;Jhooty and McKeen 1965;Peries 1962).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation